Some New Views on the Payback Period and Capital Budgeting Decisions - Weingartner, H. Martin (Management Science, 1969)
The Payback Period has been dismissed as misleading and worthless by most writers on capital budgeting at the same time that businessmen continue to utilise this concept. This paper seeks to identify the problems which businessmen try to solve by use of the payback period, so that better tools can be provided for solving these, since neither the present value nor the internal rate of return does so. In the course of the analysis the payback concept is considered in its role as a criterion versus a payback constraint, payback and liquidity of capital assets and the liquidity requirements of the firm, payback as a break-even concept, and payback as a crude measure of the rate of resolution of uncertainty. While payback is not advocated for capital investment decisions, the reasons for its popularity need to be understood before it is possible to develop superior alternatives.